High performance water-based paints with non-toxic anticorrosive pigments - del Amo, Delia Beatriz (2002)
Legal restrictions have impelled the replacement of solvent-borne resins and of toxic chromates and lead-bearing pigments in the elaboration of paints. Water-based anticorrosive paints have come a long way to improve their efficiency but their behaviour is said to be poorer than that of solvent-based paints. Nevertheless, recent advances in water-borne technologies have now resulted in improved resin systems that may be employed to produce heavy-duty coatings. The objective of this paper is to formulate high performance water-borne paints pigmented with non-toxic phosphate inhibitors. The anticorrosive properties of the paints were evaluated by accelerated tests (salt spray and humidity cabinets) and electrochemical tests (electrochemical impedance spectroscopy, EIS). The anticorrosive properties of the pigments were also evaluated by electrochemical tests. It was found that it is possible to formulate high performance anticorrosive paints by selecting adequate water-borne resins and ecological pigments.